Role of heat shock proteins 70/90 in exercise physiology and exercise immunology and their diagnostic potential in sports - Krüger, K.; Reichel, T.; Zeilinger, C. (Journal of Applied Physiology, 2019)
Heat shock proteins (HSPs) are molecular chaperones facilitating the unfolding or folding of secondary structures of proteins, their client proteins, in cellular stress situations. Various internal and external physiological and mechanical stress factors induce a homeostatic imbalance, followed by an increased expression of HSP70 and HSP90. Exercise is a stress factor, too, and its cumulative physiological perturbation manifests at a cellular level by threatening the protein homeostasis of various cell types. Consequently, an increase of HSP70/90 was described in plasma and mononuclear cells and various organs and tissues, such as muscle, liver, cardiac tissue, and brain, after an acute bout of exercise. The specific response of HSP70/90 seems to be strongly related to the modality of exercise, with several dependent factors such as duration, intensity, exercise type, subjects' training status, and environmental factors, e.g., temperature. It is suggested that HSP70/90 play a major role in immune regulation and cell protection during exercise and in the efficiency of regeneration and reparation processes. During long-term training, HSP70/90 are involved in preconditioning and adaptation processes that might also be important for disease prevention and therapy. With regard to their highly sensitive and individual response to specific exercise and training modalities, this review discusses whether and how HSP70 and HSP90 can be applied as biomarkers for monitoring exercise and training.